6 Correlation between incidental coronary calcification on non-gated CTs with findings at angiography. (October 2018) - Kelly, S; McInerney, A; Walsh, M; Jefferies, J; Kerins, D; Vaughan, C
Abstract : Introduction: Coronary calcification is frequently reported on non-gated CT thoraces performed for various indications. It remains unclear what further investigations (if any) are warranted when this finding is reported. In our institution we perform diagnostic coronary angiograms on patients with significant coronary calcification on non-gated CT thorax. We decided to review the angiographic findings to determine the accuracy of detection of significant coronary artery disease on non-gated CT thorax. Methods: All coronary angiograms performed for the incidental finding of coronary calcification on non-gated CT thorax between November 2017 and March 2018 were reviewed. Demographics, findings and patient management plans were obtained. Corresponding non-gated CT thorax reports were obtained, reviewed and correlated with angiographic findings. Results: Eight patients had a coronary angiogram performed due to incidental coronary calcification on CT thorax (7) or CTPA (1). 50% were male. The average age was 64 years (range 50–77). Indications for CT thorax were COPD (4), interstitial lung disease (1), sarcoidosis (1), recurrent infections (1) and pulmonary embolism (1). Coronary calcification was reported as 'heavy' in 5 patients and unspecified in 3. Seven reports identified multi-vessel disease. Four referred to the vessels most affected: LAD (4) and LMS (2). Many patients had known cardiovascular risk factors; hypertension 75%, hyperlipidaemia 75%, diabetes mellitus 25% and smoking history 50%. 87.5% were overweight. Coronary angiogram was performed via the radial artery in 6 cases and femoral artery in 2 cases. Seven (87.5%) patients were found to have coronary artery disease. Four had mild non-obstructive disease warranting medical management only. Three (37.5%) patients had significant coronary artery disease; two requiring PCI and one being medically managed. Both PCIs correlated were reported 'heavily' calcified on CT thorax. No patient had a complication from their diagnostic coronary. Discussion: Coronary artery calcification is often reported on non-gated CT thoraces. Although there is emerging evidence that incidentally detected coronary calcification can predict adverse cardiovascular outcomes in small single centre studies, it remains unclear what further investigations should be performed in this cohort. Our study demonstrates a high positive correlation between the findings on non-gated CT thoraces and the presence of atheroma on coronary angiogram, however, there is poor correlation with the severity of the atheroma with only 37.5% having disease warranting treatment. The risk: benefit ratio of subjecting all patients with incidental coronary calcification on non-gated CT thorax to invasive coronary angiography has yet to be defined. Conclusion: While the identification of coronary calcification on non-gated chest CT has a low correlation with significant coronary artery disease in this study, the identification of coronary calcification by non-gated CT thorax may provide an opportunity for early intervention and risk factor modification.